Social learning through water games in the field - Bernal-Escobar, Adriana; Cárdenas, Juan-Camilo; Domenech, Laia; Meinzen-Dick, Ruth S.; Sarmiento, Paula J. (World Scientific Publishing, 2025)
Economic experiments have traditionally been used as a tool for measuring human behavior in different contexts of social interaction. However, little has been discussed so far on the role of experiments as tools for learning and social change. We conducted a series of educational interventions in two municipal aqueducts in Guasca, Colombia using an irrigation collective action game where five people must decide over contributions to produce water and decide on the sequential allocation of the resource over an irrigation system. We used this setting as a pedagogical tool for understanding the effects of learning over a series of repetitions of these experiments to explore changes in the behaviors and attitudes of rural households in the sample. We ran two waves of games a few months apart with most of the same sample of 200 participants. In one of these aqueducts, we held workshops with the community to provide feedback on the results of the games. In both waves of the experiments, we find a powerful effect of face-to-face communication to improve both group efficiency in the provision of water and fairness in its distribution. Our results suggest that there are processes of learning from one wave to the next that could provide valuable lessons about the possibilities and difficulties that collective action faces within communities. In particular, we find that the workshop for discussing the results may have an effect on creating a better climate for the next wave of games, particularly with respect to average contributions and fair allocation across players. A combination of the experiments and the workshop increased individual cooperation levels, while also inducing upstream players to restrain themselves in extracting water, allowing players downstream to acquire more of the resource.